Antiparasitic Activity of Tea Tree Oil (TTO) and Its Components against Medically Important Ectoparasites: A Systematic Review - Solomon Abrha Bezabh; Wubshet Tesfaye; Julia K. Christenson; Christine F. Carson; Jackson Thomas (MDPI AG, 2022)
Ectoparasites are pathogens that can infect the skin and cause immense pain, discomfort, and disease. They are typically managed with insecticides. However, the fast-emerging antimicrobial resistance and the slow rate of development of new bio-actives combined with environmental and health concerns over the continued use of neurotoxic insecticides warrant newer and alternative methods of control. Tea tree oil (TTO), as an alternative agent, has shown remarkable promise against ectoparasites in recent studies. To our knowledge, this is the first systematic review to assess preclinical and clinical studies exploring the antiparasitic activity of TTO and its components against clinically significant ectoparasites, such as Demodex mites, scabies mites, house dust mites, lice, fleas, chiggers, and bed bugs. We systematically searched databases, including PubMed, MEDLINE (EBSCOhost), Embase (Scopus), CENTRAL, Cochrane Library, CINAHL, ScienceDirect, Web of Science, SciELO, and LILACS in any language from inception to 4 April 2022. Studies exploring the therapeutic activity of TTO and its components against the ectoparasites were eligible. We used the ToxRTool (Toxicological data reliability assessment) tool, the Joanna Briggs Institute (JBI) critical appraisal tools, and the Jadad scale to assess the methodological qualities of preclinical (in vitro and in vivo) studies, non-randomised controlled trials (including cohort, case series, and case studies), and randomised controlled trials, respectively. Of 497 identified records, 71 studies were included in this systematic review, and most (66%) had high methodological quality. The findings of this review revealed the promising efficacy of TTO and its components against ectoparasites of medical importance. Most importantly, the compelling in vitro activity of TTO against ectoparasites noted in this review seems to have translated well into the clinical environment. The promising outcomes observed in clinical studies provide enough evidence to justify the use of TTO in the pharmacotherapy of ectoparasitic infections.